GE_GERICHTE P/26152/2022 vom 29. Oktober 2024 - GE Cour de justice (2024)
RISQUE DE COLLUSION;RISQUE DE RÉCIDIVE;MESURE DE SUBSTITUTION À LA DÉTENTION;PROLONGATION | CPP.221.al1.letb; CPP.221.al1.letc; CPP.237